2013
DOI: 10.1111/jam.12318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of initial adhesion of oral bacteria through a lectin fromBauhinia variegataL. var. variegata expressed inEscherichia coli

Abstract: Aims: The aim of the present work was to study the in vitro effect of native and recombinant Bauhinia variegata var. variegata lectins in inhibiting early adhesion of Streptococcus mutans, Streptococcus sanguis and Streptococcus sobrinus to experimentally acquired pellicle. Methods and Results: Native lectin from B. variegata (BVL) was purified by affinity chromatography of extract of seeds. The recombinant lectin (rBVL-I) was expressed in E. coli strain BL21 (DE3) from a genomic clone encoding the mature B. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
0
20
0
3
Order By: Relevance
“…Some studies demonstrated that components of the bacterial cell wall, such as lipopolysaccharides (LPS), peptidoglycans and teichuronic and teichoic acids, are responsible for the antibacterial effects of lectin (Klafke et al, 2013). In the other hand, A. jiringa seed lectin presented higher levels of antimicrobial activity against gram-positive bacteria than against gram-negative bacteria (Charungchitrak et al, 2010), demonstrating that lectin acts against all bacteria groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies demonstrated that components of the bacterial cell wall, such as lipopolysaccharides (LPS), peptidoglycans and teichuronic and teichoic acids, are responsible for the antibacterial effects of lectin (Klafke et al, 2013). In the other hand, A. jiringa seed lectin presented higher levels of antimicrobial activity against gram-positive bacteria than against gram-negative bacteria (Charungchitrak et al, 2010), demonstrating that lectin acts against all bacteria groups.…”
Section: Discussionmentioning
confidence: 99%
“…The (sugar) cores of E. coli and S. enterica, for example, are composed of the common hexoses, glucose, galactose, and N-acetylglucosamine (Klafke et al, 2013), two of which are CqLec-specific. The concentration needed for bacterial growth inhibition by CqLec is similar to those presented by Indigofera …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on this subject also failed to respond effectively, and the physiological role of lectins are against the caries process. Some authors suggest various proposals regarding to this question and present meaningful data, especially with regard to the actions of lectins of higher plants Cavalcante et al, 2011;Klafke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Few novel composition found in plants are useful in the condition of cancer, immunosuppression, uncontrolled proliferation and angiogenesis [10,11,12]. Highest antioxidant potential was found in stem bark extracts of B. variegata [13,14,15]. Studies showed significant antioxidant activities of these B. variegata and suggested that it showed pronounced cytotoxic effect against DU-145, HOP-62, IGR-OV-1, MCF-7, and THP-1 human cancer cell lines with 90-99% cell growth inhibitory activity.…”
mentioning
confidence: 99%